Church mothers of Mbare Township: In memory of Mrs Elizabeth Maria Ayema (Mai Musodzi) and Sr Barbara Tredgold - Gundani, Paul H. (HTS teologiese studies, 2019)
The changing of place names (e.g. street and public buildings) often accompanies change of governments, particularly in countries where one ideology has triumphed over another. This was the case in Zimbabwe following the triumph of ZANU-PF over the settler colonial government of Ian Smith, in 1980. Harari Township, the oldest black suburb in the then city of Salisbury (also renamed Harare), underwent name change in 1982 and was renamed Mbare. Public consultations by the City Council resulted in the changing of the street names that brought about a changeover in Township’s ondonyms. Streets and public buildings were renamed after persons who had made outstanding contribution to the development of the Township. Among those honoured were two outstanding female Christian leaders, Mrs Elizabeth Maria Ayema (popularly known as Mai Musodzi) and Barbra Tredgold. Incidentally, these were the only two women after whom a street and a public amenity were named. In this article, we investigate the contribution that these two women made to Mbare Township to deserve the honour bequeathed on them by the residents of Mbare. In the article, we acknowledge that Mai Musodzi and Barbara Tredgold were honoured because they were among the illustrious leaders, who served the Township with distinction. By honouring their memory, residents of Mbare were, by implication, making a commitment to live by the values that the two stalwarts stood for. In our conclusion, we argue that the tribute accorded to the two reflects the consensus of the residents of Mbare that Christian values that the two had lived by were an important site of struggle for marginalised black people, who made the ghetto-like ‘Location’ a homely habitat.